Thoracic surgeryPractical comments on recurrent laryngeal nerve neuromonitoring during thyroid surgery - Masiak-Segit, Wioletta; Dąbrowski, Andrzej; Abramowicz, Krystyna; Jaworski, Tomasz Jerzy; Wallner, Grzegorz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Neuromonitoring (intraoperative neurophysiological monitoring – IONM) is a new non-invasive technique, which does not place any additional strain on the patient. The surgeon uses a stimulation probe to search for the recurrent laryngeal nerve within the surgical site. IONM provides auditory and visual cues when the probe is in the vicinity of the nerve. During the stimulation of the nerve, vocal muscles are stimulated as well, which causes the vocal cords to tighten to the rhythm of the electric pulses fed to the recording electrode attached to the endotracheal tube. Neuromonitoring requires close cooperation between the surgeon and the anesthesiologist. IONM cannot serve as a substitute for technical skills and thorough knowledge of neck anatomy. Its use significantly improves patient safety and the comfort of the surgeon. Based on the literature and their own experience, the authors of the article describe the standards of the neuromonitoring procedure, the problems that may occur during its use, as well as solutions for these problems.